Alfuzosin versus tamsulosin for symptomatic benign prostatic hyperplasia: a prospective comparative study - Noor Husain; Prabhat Kumar Agrawal; Ahsan Ahmad; Raj Narayan Seth (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Benign prostatic hyperplasia (BPH) is a common cause of lower urinary tract symptoms (LUTS) in aging men. Alpha-1 adrenergic receptor antagonists are recommended as first-line pharmacological therapy. This study compared the efficacy and safety of alfuzosin and tamsulosin in men with symptomatic BPH. Methods: In this prospective, open-label, comparative study, 60 men with symptomatic BPH were allocated to receive either alfuzosin 10 mg once daily (n=30) or tamsulosin 0.4 mg once daily (n=30) for 12 weeks. International Prostate Symptom Score (IPSS), maximum urinary flow rate (Qmax), and post-void residual urine volume (PVRU) were assessed at baseline, 4 weeks, and 12 weeks. Adverse events were recorded throughout the study. Results: Baseline characteristics were comparable between groups. Both treatments produced significant improvement in IPSS, Qmax, and PVRU from baseline to 12 weeks (all p